Valuing ‘Green Infrastructure’ in Jeddah: A City lost in ‘Grey’ Infrastructure - Aljoufie, Mohammed; Tiwari, Alok (Journal of Architecture and Urbanism, 2015)
In the planning of the urban green infrastructure it is important how the decision makers and residents value their living environment. While the coverage of Green Infrastructure in the case of Jeddah appears negligible, the paper attempts to find out its causal factor. We primarily consider (1) what are the challenges of resident's well-being in Jeddah which Green Infrastructure can solve. (2) What are the constraints; obstructing the sustainable expansion and development of green infrastructure in Jeddah and (3) what are the policy interventions required as well as crucial issues to be considered while planning of green infrastructure in Jeddah. Primary data through satellite imagery and secondary data from extensive literature search incorporating internal and external linkages on the problems; could generate further discussion on the way by which green infrastructure planning could be successfully loomed.